The Influence of Madrasah Head Supervision on Teacher Performance - Hikma Hikma; Sagaf S. Pettalongi; Masmur M. (Urwatul Wutsqo: Jurnal Studi Kependidikan dan Keislaman, 2026)
The goal of this study was to ascertain how the madrasah principal's supervision affected the performance of the teachers at Madrasah Tsanawiyah Negeri 3 Palu City. The methodology utilised in this investigation was quantitative. The study population consisted of forty instructors from Madrasah Tsanawiyah Negeri 3 Palu City. Because saturated sampling was the sampling approach employed, the entire population served as the research sample. In order to gather data for this study, questionnaires were distributed. Data analysis and instrument testing were conducted using SPSS Statistics software. Data analysis techniques included descriptive analysis, inferential statistical analysis (normality and linearity tests), simple linear regression testing, hypothesis testing, and determination coefficient testing. The study's findings demonstrated that the madrasah principal's oversight had a major impact on teachers' performance. This was demonstrated by the R Square value of 0.340, which showed that the madrasah principal's supervision had an impact on 34% of teacher performance, while other factors not covered in this study had an impact on the remaining 66%. These results demonstrate that teacher performance at Madrasah Tsanawiyah Negeri 3 Kota Palu is greatly enhanced by the principal's supervision.